The Social Dimensions Of Understanding The Art Of Literary Language (Texas Journal of Philology, Culture and History, 2025)
The article analyses the principles of social and political factors in the creation of literary or poetic language. The art of literary literature has a generalizing character, because artistic work involves any aspect of social life in the process of realizing the realities of reality and characters. The article says that the concept of imagination is the unique stages of the concept of imagination within the hermenevatic analysis of the artistic literature. This is an important part of human being as the result of a psychological manual process. The processes in man contain a reflection of emotionality. All incoming incidents in the human imagination remain a separate autonomous world to everyone. It is possible to understand the owner of the imagination only through written or verbally. Imagination Everyone is analyzed as a proof of their spiritual freedom. The most important fact here is freedom of imagination. No one can ever involve a world of imagination, but cannot occupy it. It has the ability to create or live free and free. Based on this principle, again approved the imagination is appropriate to talk about its internal construction and its stages.